A Review on Relevance of Pramana Pariksha (Physical Anthropometry) (International Journal of Ayurveda and Pharma Research, 2023)
The estimation of Bala on the basis of Pramana (Physical anthropometry) is one of the glorious concepts of Ayurveda. The Pareeksha of Atura Deha before performing his Chikitsa plays a significant role in the proper assessment of Rogi with respect to his Bala and Ayu. Pramana (physical anthropometry) is mainly assessed by Swa-Angula, which is taken as the unit of measurement of the body parts and structures with respect to length, breadth, height, and circumference. Anthropometry explains about average height, and breadth of a person and his body parts with the help of different measuring units like cm, inch, etc, but applying average will not serve the purpose in every situation as anthropometric measurements are supposed to get influenced by different circumstances like gender, race, place and time, etc. The “Swa-Angula Pramana (physical anthropometry)” is an ideal parameter irrespective of gender, race, and place. The growth of the body varies at different ages and gets ceased after a particular stage. Anguli Pramana (physical anthropometry) is a unit of measure followed in the olden days to denote the dimensions of any object which includes Ayama (length), Vistara (width), Parinaha (circumference), Utsedha (height), etc. An individual with Anga-pratyangas having proper measurements is endured with longevity, wealth, prosperity, happiness, Ojas, strength, etc.